The unconstitutionality of the changes to the death pension: (resulting from the modifications promoted by Law nº 13.135/2015 in article 77 of Law nº 8.213/1991) (Revista do Tribunal Regional Federal da 3ª Região, 2017)
Based on an exclusively positivist analysis, as is common knowledge, the case law of the higher courts has established that the death pension is governed by the legislation in force at the time of the insured's death. Even if one disagrees with this premise, there is no disputing it, since it is a long-standing jurisprudential understanding. Therefore, in the case of deaths after the advent of Law No. 13,135/2015, the important (and restrictive) changes it made to article 77 of Law No. 8,213/1991 must be taken into account. However, as we will see below, the requirements demanded by paragraph 2 of article 77 of the new legislation do not stand up to a more accurate constitutional analysis. Therefore, any sentence, including those of the first instance in a diffuse control of constitutionality, can set aside, as unconstitutional, the new provisions introduced in article 77, paragraph 2, of the Benefits Law, stating that pensions for death will be granted without any time limitation for their duration, therefore, in compliance with the Constitution of the Federative Republic of Brazil, and will always be for life.
Keywords: death pension; Law no. 13.135/2015; inconstitutionality